Vector control of an AC brushless servomotor using a custom-designed motion control card - Zorlu, Sibel; Senol, Ibrahim; Bakan, A. Faruk (IEEE, 2006)
In this study, vector control of an AC brushless servomotor is performed using the current controlled, voltage source inverter and hysteresis PWM method. Using vector control, three phase variables are transformed on the synchronously rotating d and q axis, and control can be performed as in the DC motor. In order to generate PWM signals, an error value is calculated by comparing the current reference and actual current, and it is used as an input for hysteresis control. Then, the voltage vector is obtained, and the motor is driven by using the inverter to follow current reference values. Finally the servomotor speed is controlled by using this card, and results are presented. Using this custom-designed motion control card, high performance drive systems and complex algorithms can be developed. Since the proposed control system is very flexible, it is also applicable for studies on sensorless servomotor control by only modifying the software. Therefore in this paper, sensorless speed control results with ANN are also presented.
Keywords: SENSORLESS CONTROL; MOTOR DRIVE; Automation & Control Systems; Computer Science; Engineering